Impact of COVID-19 pandemic on medicine supply chain for patients with chronic diseases: Experiences of the community pharmacists - Manasvini Ramakrishnan; Pooja Gopal Poojari; Muhammed Rashid; Sreedharan Nair; Viji Pulikkel Chandran; Girish Thunga (Elsevier, 2023)
Problem considered: Coronavirus disease(COVID-19) outbroke towards the end of December 2019 in China, soon it started spreading rapidly to various countries leading to an outburst of pandemic. Due to the restrictions imposed to control the spread of the infection, globally the manufacturing, import and export of medicine and the healthcare services to patients with chronic illness had been affected. This study aimed to explore the perspectives of the pharmacists on the medicine supply chain for patients with chronic diseases during COVID-19 pandemic in India. Methods: This study is a prospective, qualitative research involving telephonic, semi-structured in-depth interviews. An interview guide for pharmacists was prepared and validated using "Interview Protocol Refinement" method. Purposive sampling method was used to recruit the pharmacists; a telephonic oral consent was obtained. The interview session was audio recorded and the recordings were transcribed verbatim. Further, transcripts were validated and later analysed using NVivo software. Results: A total of 8 participants were interviewed during our study. Thematic analysis of the transcripts resulted in seven main themes. The study showed that there was deficiency in medicine supply during the COVID-19 pandemic and the pharmacists faced several challenges in procuring and storing the medication, arranging for unavailable medicines, medication dispensing and provision of the services such as medicine delivery, patient counselling. There was also scarcity of manpower leading to extra workload and working overtime. Conclusion: Uninterrupted supply of essential medicine is the backbone of health care system. An effective plan and appropriate strategies are vital to combat such future emergencies.